PENGARUH EVA, OPERATING CASH FLOW, EPS, RESIDUAL INCOME, & OPERATING LEVERAGE TERHADAP RETURN SAHAM DI PERUSAHAAN FARMASI YANG TERDAFTAR DI BEI 2012-2016 - NURMALIA, ERLINA; SISTA PARAMITA, R.A. (Jurnal Ilmu Manajemen (JIM), 2020)
The capital market is a means for fund owners or investors to carry out invest in companies that need funds. The purpose of this study is as follows to analyze the effect of economic value added (EVA), operating cash flow, residual income, earnings per share (EPS), operating leverage on stock returns on pharmaceutical companies listed on the Indonesia Stock Exchange 2012-2016. In this study using explanatory research with a quantitative approach, because in this study the method used is the explanation method. The population is all pharmaceutical companies listed on the Indonesia Stock Exchange during the period 2012-2016 with a population of 9 companies. The sampleselection is done by non probabilit sampling technique, which is a sampling technique that does not provide equal opportunity or opportunity for each element or member of the population to be selected as a sample. In this study using multiple regression analysis with the help of SPSS application version 24.0. The results of this study are: Economic Value Added, Residual income, Earning Per Share, Operating Leverage does not affect stock returns in pharmaceutical companies listed on the Indonesia Stock Exchange 2012-2016. Operating cash flow has an effect on stock returns in pharmaceutical companies listed on the Indonesia Stock Exchange 2012-2016. Keywords: economic value added; earning per share; operating cash flow; operating leverage; residual income; stock return.